The molecular signature of AML with increased ALDH activity suggests a stem cell origin - Blume, Rachel; Rempel, Eugen; Manta, Linda; Saeed, Borhan R.; Wang, Wenwen; Raffel, Simon; Ermakova, Olga; Eckstein, Volker; Trumpp, Andreas; Ho, Anthony Dick; Lutz, Christoph (Leukemia and lymphoma, 2018)
Enrichment of leukemic blasts with a stem cell phenotype correlates with poor survival in acute myeloid leukemia (AML). In this context, measurement of the stem cell marker aldehyde-dehydrogenase (ALDH) activity can distinguish poor prognosis cases with increased fractions of ALDH-positive cells (ALDH-numerous AML) and favorable outcome cases with low percentages (ALDH-rare AML). It has been shown that ALDH-numerous AML favor leukemic engraftment in xenotransplantation assays which suggests increased leukemic stem cell (LSC) potential. To test if this reflects an immature cell of origin, comparative gene-expression studies of CD34+ leukemic blasts were performed. This analysis revealed increased expression of LSC and HSC signatures in ALDH-numerous AML, whereas ALDH-rare AML were enriched for a progenitor signature. The enrichment of stemness-associated transcriptional programs suggests that ALDH-numerous AML derive from immature hematopoietic progenitors and offers an explanation for the poor prognosis and therapy resistance of this subgroup which is likely caused by inherited stem cell properties.
Gesehen am 22.10.2019